Introduction (Scottish Historical and Archaeological Internet Reports, 2013)
Lying between Arthur's Seat and Calton Hill, the Canongate is situated on the lower part of the crag and tail feature created by the glacial obstruction of the Castle Rock. Both excavations were located in peripheral zones of medieval and post-medieval backland activity.